Assessment of the interactions between pea and salivary proteins in aqueous dispersions. (March 2023) - Assad-Bustillos, M.; Cázares-Godoy, A.C.; Devezeaux de Lavergne, M.; Schmitt, C.; Hartmann, C.; Windhab, E.
Abstract: To understand and limit the unpleasant oral sensation of astringency felt during the consumption of pea-based drinks, we investigated the interaction between mixtures of salivary and pea proteins, as compared to mixtures where HEPES buffer (at pH 6.8) was used as a negative control for saliva. Since astringent compounds have the ability to bind with salivary proteins, mixes of freshly collected whole unstimulated saliva and a pea protein isolate (PPI) (a dispersion at 3.5% w / v ) were prepared in ratios 95:5 and 1:1 saliva:PPI, to allow different stoichiometries to occur in the mouth. Samples were incubated at 37 °C during 30 min, after centrifugation at 16000 g during 20 min to separate pellet from supernatant. Using techniques such as SEC, Native-PAGE and LC-MS, 7 pea proteins were identified as being capable of forming aggregates with at least 7 saliva proteins, some of which have been previously connected to astringency. Graphical abstract: Unlabelled Image Highlights: Pea proteins (PP) and salivary proteins (SP) are able to form aggregates and precipitate. 7 different PP formed aggregates with at least 7 SP. Legumins, Vicilins and Albumins were involved in the aggregate formation with SP. Aggregates had MW of 180 and 310 kDa. Most of the SP precipitated have been previously connected to astringency.